STRATEGI KOPING KARYAWAN YANG MENGALAMI PHK DI MASA PANDEMI - Bella Saviera; Zahrotur Rusyda Hinduan; Zainal Abidin (Psyche: Jurnal Psikologi, 2022)
The Covid-19 pandemic has a significant impact for individuals, especially in employees. Some companies have reduced the number of employees so that employees have to experience layoffs (PHK). As for the effect that can arises from layoffs, such as depression and anxiety, therefore it takes a coping strategies to be able reduce the impact. The purpose of this study is to see how coping strategies are used by employees to survive and face problems, and how the ability of employees to find new jobs after being layoff during a pandemic period. This study used a qualitative research method, using a case study. Participants in this study were 3 individuals with the criteria of employees who experienced layoffs during the pandemic. Data collection using semi-stuctured interviews. The results of this study found that the strategies coping used by the subjects were dominant in problem focused coping.